Effects of bowel cleansing on the intestinal microbiota. Issue 10 (19th December 2014) - Jalanka, Jonna; Salonen, Anne; Salojärvi, Jarkko; Ritari, Jarmo; Immonen, Outi; Marciani, Luca; Gowland, Penny; Hoad, Caroline; Garsed, Klara; Lam, Ching; Palva, Airi; Spiller, Robin C; et al.
Abstract : Objective: An adequate bowel cleansing is essential for a successful colonoscopy. Although purgative consumption is safe for the patient, there is little consensus on how the intestinal microbiota is affected by the procedure, especially regarding the potential long-term consequences. Design: 23 healthy subjects were randomised into two study groups consuming a bowel preparation (Moviprep), either in two separate doses of 1 L or as a single 2-L dose. Participants donated faecal samples at the baseline, after bowel cleansing, 14 and 28 days after the treatment. The intestinal microbiota composition was determined with phylogenetic microarray as well as quantitative PCR analysis and correlated with the previously quantified faecal serine proteases. Results: The lavage introduced an instant and substantial change to the intestinal microbiota. The total microbial load was decreased by 31-fold and 22% of the participants lost the subject-specificity of their microbiota. While the bacterial levels and community composition were essentially restored within 14 days, the rate of recovery was dose dependent: consumption of the purgative in a single dose had a more severe effect on the microbiota composition than that of a double dose, and notably increased the levels of Proteobacteria, Fusobacteria and bacteria related to Dorea formicigenerans. The abundance of the latter also correlated with the amount of faecal serine proteases that were increased after purging. Conclusions: Our results suggest that the bowel cleansing using two separate dosages introduces fewer alterations to the intestinal microbiota than a single dose and hence may be preferred in clinical practice.